2021
DOI: 10.1136/bmjdrc-2020-001698
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cells from both innate and adaptive immunity with lower nerve conduction velocity: the Maastricht Study

Abstract: IntroductionDistal sensorimotor polyneuropathy (DSPN) is common in people with diabetes but is also found in pre-diabetes. Peripheral nerve myelin damage, which can be assessed by reduced nerve conduction velocity (NCV), is an essential feature of DSPN. Emerging evidence indicates that the development of DSPN may involve the activation of the immune system. However, available studies have mainly investigated circulating immune mediators, whereas the role of immune cells remains unclear. Therefore, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(53 reference statements)
0
3
0
1
Order By: Relevance
“…We constructed an ‘MNCV sum score’ based on MNCVs, an ‘SNCV sum score’ based on SNCVs, and a ‘total NCV sum score’ based on MNCVs, SNCVs and SNAPs. The sum scores combine information about the NCVs of different nerves by giving equal weight to each nerve, allowing for a more comprehensive assessment of nerve function in an individual [ 39 , 40 ]. Primary analyses addressing a pre-planned hypothesis on NFL with primary and secondary exploratory endpoints were not adjusted for multiple testing.…”
Section: Methodsmentioning
confidence: 99%
“…We constructed an ‘MNCV sum score’ based on MNCVs, an ‘SNCV sum score’ based on SNCVs, and a ‘total NCV sum score’ based on MNCVs, SNCVs and SNAPs. The sum scores combine information about the NCVs of different nerves by giving equal weight to each nerve, allowing for a more comprehensive assessment of nerve function in an individual [ 39 , 40 ]. Primary analyses addressing a pre-planned hypothesis on NFL with primary and secondary exploratory endpoints were not adjusted for multiple testing.…”
Section: Methodsmentioning
confidence: 99%
“…The gating strategies for flow cytometry of whole blood and aSAT are reported in Supporting Information Figures S1 and S2, respectively. The antibodies and gating strategy for flow cytometry for the Maastricht Study were similar, as reported elsewhere [20]. All samples were measured with a FACS-Canto II (BD Biosciences) and analyzed with FACSdiva software (BD Biosciences).…”
Section: Asat Biopsymentioning
confidence: 99%
“…These cutaneous changes can contribute to the development of skin fissures, producing susceptibility to microorganisms in the context of an already deregulated immune system 181 . Some studies suggest altered leukocyte composition in association with development of diabetic peripheral neuropathy, with increased neutrophil‐to‐lymphocyte ratio and increased basophil and CD4+ T‐cell populations 182,183 . Diabetic patients demonstrate significantly decreased periglandular nerve terminals, 184 and various neuropathy screening methods have found asymmetry of sensorimotor neuropathy between extremities to correlate with disease severity and DFUs 185,186 …”
Section: Microvasculature Changes and Peripheral Neuropathy Due To Di...mentioning
confidence: 99%